Matrix isolation studies of carbonyl selenide, OCSe: Evidence of the formation of dimeric species, (OCSe)2 - Gómez Castaño, Jovanny Arles (2014)
OCSe isolated in solid Ar or N2 at 10 K was investigated by FTIR spectroscopy. The IR spectra of OCSe diluted in a 1:1000 proportion with the matrix gases were interpreted in terms of monomeric carbonyl selenide in a single matrix site. The IR spectra of more concentrated matrices revealed several new IR absorptions, which were tentatively assigned to different dimeric structures, aided by the prediction of quantum chemical calculations. The different matrices were exposed to UV–visible broad-band radiation, finding that monomeric OCSe decomposes into CO and Se, as evidenced by the IR absorption of CO perturbed by the presence of a selenium atom in the same matrix cage, while dimeric forms of OCSe decompose giving mainly (CO)2.